2019
DOI: 10.1108/jes-11-2017-0334
|View full text |Cite
|
Sign up to set email alerts
|

Strategy, tax planning and liquidity constraints in investment funds

Abstract: Purpose The purpose of this paper is to analyze the effect of the interaction between liquidity constraints and tax planning on the performance of Brazilian investment funds, since liquidity constraints reduce precipitated withdrawals, allowing tax planning operationalization. Design/methodology/approach The sample of this study is comprised of 8,008 Brazilian multimarket funds, considering the period from January 2004 to September 2017. The authors considered tax planning, lockup periods and minimum balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Pajak merupakan perencanaan yang sangat penting dalam keputusan keuangan (Malaquias & Martins Borges Junior, 2019). Dari beberapa pengertian pajak yang telah diuraikan, maka dapat penulis simpulkan bahwa pajak adalah iuran wajib rakyat kepada negara yang bersifat memaksa dan tidak mendapat jasa imbalan yang langsung digunakan untuk membiayai pengeluaran-pengeluaran negara.…”
Section: Tax Terhadap Dividend Payout Ratiounclassified
“…Pajak merupakan perencanaan yang sangat penting dalam keputusan keuangan (Malaquias & Martins Borges Junior, 2019). Dari beberapa pengertian pajak yang telah diuraikan, maka dapat penulis simpulkan bahwa pajak adalah iuran wajib rakyat kepada negara yang bersifat memaksa dan tidak mendapat jasa imbalan yang langsung digunakan untuk membiayai pengeluaran-pengeluaran negara.…”
Section: Tax Terhadap Dividend Payout Ratiounclassified
“…The results indicated that investment funds that implemented, at the same time, redemption restrictions and tax planning presented higher risk-adjusted return rates. As robustness tests, Malaquias and Borges Júnior (2019) also considered samples composed only of funds with a positive Sharpe ratio and fund rankings ordered by Sharpe ratio. However, the results were not robust for these different performance measures.…”
Section: Investment Fund Performance Evaluationmentioning
confidence: 99%
“…Oliveira Filho and Sousa (2015) point out as the main limitation the possibility of obtaining estimates from negative values, which makes comparisons unfeasible, as the ordering rule may not make logical sense, since funds with higher risk would be classified as better ones. Thus, some studies have opted to exclude funds with a negative Sharpe ratio from the sample when evaluating funds' performance, such as Malaquias and Borges Júnior (2019).…”
Section: Investment Fund Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation